C’s Dynamic Memory Allocation Assisting AI Model Training Dataset AI Embedded Systems use concepts of C’s Dynamic Memory Allocation (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Embedded AI devices operate under tight resource constraints (limited RAM, CPU, and power), yet they need to run inference efficiently. Dynamic memory allocation and dynamic variables play a crucial role here. Embedded systems often use C for AI deployment, so dynamic memory management (malloc, calloc, realloc, free) is central for ‘Model Parameter Storage’, ‘Input Buffers for Sensor Data’, ‘Batch Processing and Streaming’, ‘Memory Pooling’, ‘Dynamic variables for adaptability’.